Contract Marriage in Indonesia: Controversial and Contemporary Issue on Law and Its Impact - Akrimatil Izat (Universitas Negeri Semarang, 2020)
A marriage contract is a temporary marriage in accordance with an agreed contract between the bride and groom and will end by itself if the contract is exhausted. Indonesia as a country that upholds religious values and norms of society is certainly very critical in determining the validity of a marriage. Marriage of contracts in Indonesia is difficult to record. Because the marriage of the contract is carried out in addition to not being recorded by formal judicial is not regulated in any regulation so it can be said that the marriage contract in Indonesia is not recognized and does not apply the law. Also in Islamic law also does not allow the existence of contract marriage is based on the words of the Prophet SAW. The marriage of the contract also has many consequences to the wife and the offspring of the marriage of the contract.